Cracking mechanism and a novel strategy to eliminate cracks in TiAl alloy additively manufactured by selective laser melting. (November 2021) - Wang, M.S.; Liu, E.W.; Du, Y.L.; Liu, T.T.; Liao, W.H.
Abstract: Additive manufacturing of TiAl alloys by selective laser melting (SLM) remains a challenge due to serious cracking during the print process. In this work, the cracking mechanism of the SLM-fabricated Ti-48Al-2Cr-2Nb alloy is studied. Experimental results show that the cracks mainly occurred in the Nb-poor regions and near the interfaces between α2 and B2 phases. A novel strategy to eliminate cracks is thus proposed: eliminating the Nb-poor regions and reducing the interface between different phases. It is found that by increasing Nb content, a nearly α2 single-phase structure without heterogeneous interface formed along with the elimination of Nb-poor regions in the SLM-fabricated Ti–48Al–2Cr–8Nb alloy. The as-SLMed alloy is crack-free and of high strength, verifying the effectiveness of the proposed strategy. Graphical abstract: Image, graphical abstract